PERENCANAAN SEAWALL MODIFIKASI POLDER BERBASIS SELF-CLOSING FLOOD BARRIER DAN SMART WATER SQUARES PADA KAWASAN PESISIR - Aziz, Hafif Ahmad Abdul; Putri, Laura Angelina Aprilianta Eka; Setiawan, Wendik; Dewi, Vita Ayu Kusuma; Dewi, Mega Septia Sarda (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
Global climate change, rising temperatures, and rising sea levels are major challenges today. Based on data from the WMO and European Union climate monitors, global temperatures have exceeded the 1.5°C threshold. Without immediate action, the impacts of climate change in coastal areas will become increasingly difficult to address, threatening the well-being of future generations. The IPCC report (2021) predicts a sea level rise of 0.29 to 0.59 meters by 2100, which will impact coastal areas, including Indonesia, with the potential for annual flash flooding by 2050. This research aims to develop innovative solutions to overcome the impact of sea level rise due to glacier melting, namely in the form of planning and Seawall design analysis with modification of polder based on self-closing flood barriers and smart water squares. The method used is research & development with Stanford's design-thinking approach, which includes analyze, define, design, implementation, and evaluation. The result is the planning and design of Seawall ideas with modifications of polder based on self-closing flood barriers and smart water squares. The system combines automatic flood closure gate technology and design for water intake, recreation, and stormwater management, to improve the protection, sustainability of ecosystems, and the quality of life of coastal communities. This research is expected to overcome the impact of sea level rise and tidal flooding, as well as strengthen resilience to climate change in coastal areas. Abstrak Perubahan iklim global, peningkatan suhu, dan kenaikan permukaan air laut merupakan tantangan besar saat ini. Berdasarkan data WMO dan pemantau iklim Uni Eropa, suhu global telah melebihi ambang batas 1,5°C. Tanpa tindakan segera, dampak perubahan iklim di wilayah pesisir akan semakin sulit diatasi, mengancam kesejahteraan generasi mendatang. Laporan IPCC (2021) memperkirakan kenaikan permukaan laut 0,29 hingga 0,59 meter pada 2100, yang akan berdampak pada wilayah pesisir, termasuk Indonesia, dengan potensi banjir rob tahunan pada 2050. Penelitian ini bertujuan mengembangkan solusi inovatif untuk mengatasi dampak kenaikan permukaan air laut akibat pencairan gletser yakni berupa analisa perencanaan dan perancangan Seawall dengan modifikasi polder berbasis self-closing flood barrier dan smart water squares. Metode yang digunakan adalah research & development dengan pendekatan design-thinking Stanford, yang meliputi analyze, define, design, implementation, dan evaluation. Hasilnya adalah perencanaan dan perancangan gagasan Seawall dengan modifikasi polder berbasis self-closing flood barrier dan smart water squares. Sistem ini menggabungkan teknologi pintu penutup banjir otomatis dan desain untuk penyerapan air, rekreasi, serta pengelolaan air hujan, guna meningkatkan perlindungan, keberlanjutan ekosistem, dan kualitas hidup masyarakat pesisir. Penelitian ini diharapkan dapat mengatasi dampak kenaikan permukaan air laut dan banjir rob, serta memperkuat ketahanan terhadap perubahan iklim di wilayah pesisir.